Epidemiological Significance of Hantavirus Infection in Crimea - L. S. Zinich; I. S. Kovalenko; N. N. Pidchenko; S. N. Tikhonov (Проблемы особо опасных инфекций, 2019)
Objective of this work was to determine epidemiological significance of Hantaviruses, circulating in Crimea, on the basis of retrospective data and taking into account the results obtained over the monitoring period of 2015–2018.Materials and methods. The study of small mammals and blood sera of donors was carried using enzyme-linked immunosorbent assay.Results and discussion. Held in 1985–1989 studies of hemorrhagic fever with renal syndrome (HFRS) suggested that Hantaviruses, circulating among the voles of the genus Microtus in the territory of Crimea, do not have etiological significance in the structure of HFRS incidence. A 2008 study found the circulation of Hantaviruses of the Tula serotype among Microtus arvalis (obscurus). Studies on the natural focality of Hantavirus infection in Crimea during 2015–2018 showed circulation of Hantaviruses among small mammals: Microtus socialis, Mus musculus, Sylvaemus witherbyi, Crocidura suaveolens, which are not the main reservoirs of pathogenic Hantaviruses. Also, seropositive to hantavirus donors were detected – 0.4 %. Local cases of HFRS infection for the entire observation period were not registered. To confirm the positive findings and determine the epidemiological significance of circulating pathogens, samples with positive for Hantaviruses findings were sent to the reference center for HFRS in 2017. The results of the investigation did not confirm the presence of antibodies to human pathogenic Hantaviruses in the blood sera of donors; in the biological material from mouse-like rodents, the antigen of pathogenic for humans serotypes of Hantavirus was not detected. Thus, in the natural foci of Crimea in 2015–2018, the circulation of Hantaviruses which do not belong to pathogenic for humans serotypes of Hantavirus Puumala, Hantaan, Dobrava was registered. Detection of seropositive donors testifies to natural immunization of the population through circulation of Hantaviruses that are non-pathogenic for humans or Hantaviruses of other serotypes.